Realities of the independence of the banco de la república (1997)
The autonomy of the Central Bank of Colombia is part of a political process which seeks to reduce Colombia' s exaggerated centralismo However, central power was not limited to a sufficient degree by the Constitution of 1991, as demonstrated by the fact that the Minister of Finance is the President of the Board of Directors of the Banco de la República. This does not happen in any independent bank in the world, because the objectives of the government are different from those of the central bank, and the Minister of Finance could divert the Bank away from its fundamental anti-inflationary objectives. This article proposes that the principle of no reelection makes the time horizon very short for the government to reap the fruits of a stabilization policy. The government tends to spend in excess in order to improve its public image, and the next government has to confrontthe maladjustment. Therefore coordination between the Central Bank and the government becomes very conflictual.